The Criminal Law Policy in Eradicating Corruption Crimes - Sagimo, Sagimo (Universitas Islam Sultan Agung, 2022)
This study aims to identify and analyze criminal law policies in eradicating corruption. This study uses a socio-juridical legal approach and the specifications in this study include analytical descriptive. Based on the results of the study, it shows that criminal law policies in eradicating corruption against perpetrators of corruption carry out several stages in accordance with statutory regulations, namely examination, investigation, investigation and prosecution. Efforts are being made to prevent corruption by means of comprehensive efforts or policies as well as overall administrative reform in the form of privatization, deregulation and decentralization. In addition, facilitation efforts through the TP4D program and through the Civil and State Administrative fields are ways and solutions in an effort to prevent budget leaks which result in losses to state finances. Obstacles to law enforcement against perpetrators of corruption are the complexity of corruption cases, time constraints, the intensity of inspections by limited functional supervisory apparatus, the spread of corruption cases through public policies, and the factor of the relatively low level of public legal awareness. The solution in overcoming obstacles to law enforcement against perpetrators of corruption is the procurement of personnel who have quality as prosecutors in the field of special crimes (corruption crimes), holding special education for assigned prosecutors and technical mastery of special criminal investigations.